The Development of Anthropology in Indonesia - Farhan Fathur Rahman; Prawira Amanda Putra Siagian (Program Pascasarjana UIN Sumatera Utara Medan, 2024)
Anthropology is a branch of social science that studies humans holistically, from cultural and social aspects, as well as the value systems that develop in society. Indonesia, as a country with diverse ethnicities, languages, customs, and social systems, is a very important area of study in the development of anthropology. This article aims to describe the history of anthropology's development, the development of anthropology in Indonesia, and its relevance in understanding the socio-cultural and legal life of society. This research uses a literature study method with a qualitative descriptive approach through data collection from books, scientific journals, and relevant literature. The research stages are carried out through source identification, data classification, content analysis, and interpretation of literature findings. The results of the study show that anthropology has developed from ethnographic records during the colonial period to a systematic and modern scientific discipline. In Indonesia, the development of anthropology underwent a significant transformation after independence through Koentjaraningrat's contribution to the institutionalization of anthropological science and strengthening of national scientific identity. The discussion emphasizes that anthropology in Indonesia is now developing on contemporary issues such as urbanization, globalization, legal pluralism, and digital culture. Thus, anthropology has a strategic role in understanding the complexity of pluralistic and dynamic Indonesian society.